Estudo quantitativo da carência e da formação de professores de ciências naturais para ensino fundamental - Pena, Samira Cristina de Santana (2017)
The objective of this research is to verify how the public policies of teacher education in Brazil have acted for the training of teachers of Natural Sciences, considering the lack of teachers that characterizes the national scenario and the term established until 2024, by the National Plan Of Education (PNE). The motivation for the realization of this research appeared during the graduation when perceiving the lack of contents destined to the teaching of Natural Sciences. This research is part of a larger project coordinated by Professor Renato Santos Araujo, who studies the public policies of teacher training in Physics, Chemistry, Biology, Natural Sciences and Mathematics with a focus on the Institutional Program of the Initiation to Teaching Grant (PIBID /CAPES). In this dissertation, part of the first stage of the larger project destined to the training of Natural Sciences teachers will be held. The work is divided into stages: first is the course of Degree in Natural Sciences throughout the twentieth century and it is observed that at the moment it is not clear in the legislation who should teach this discipline in the final years of Elementary School. This justified a bibliographical revision on the teaching of Sciences and the formation of these teachers. In this context, we sought to discuss the knowledge required for the training of these teachers, such as to know the subject, to acquire theoretical knowledge, to make use of research and innovation, to know how to evaluate and others. In this way, it was possible to draw a profile for this professional and clarify that to teach science it is necessary to have specific knowledge and practices. Next, some public policies were presented for the training of teachers, such as PIBID, PARFOR, PRODOCÊNCIA and UAB, in a kind of panorama of what was done by the rulers of this century. Methodologically, a documentary research was conducted, with a quantitative approach. The data sources used were the Statistical Synopses of Higher Education and Basic Education, published by the National Institute of Educational Studies and Research (INEP) and the CultivEduca Portal created by the Federal University of Rio Grande do Sul. The collected data inform about the courses Number of candidates, admissions, enrollments and graduates and on basic education the number of classes, teachers who teach Natural Sciences and their degrees. The data analyzes produced, among other results, estimates for the rates of evasion and estimates of the participants. This analysis was carried out through descriptive statistics and it was possible to emphasize that there was a decrease in the number of vacancies for undergraduate courses in Natural Sciences and that most of the teachers who teach this subject in Brazilian schools do not have the training required by LDB. This Degree tends to be extinguished and replaced by other degrees, such as Biological Sciences.